2018
DOI: 10.3389/fendo.2018.00679
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Goiter and Thyroid Surgery on Goiter Related Esophageal Dysfunction. A Systematic Review

Abstract: Background: Patients with goiter referred for thyroidectomy report swallowing difficulties. This might be associated with esophageal compression and deviation as this is present in a significant number of patients. Studies on how goiter and subsequently its treatment affect the esophagus are sparse and point in various directions. Our aim was to investigate, through a systematic review, the impact of goiter and thyroidectomy on esophageal anatomy, esophageal physiology, and subjective swallowing dysfunction.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Benign nodular goiter may result in a range of symptoms, including difficulties in swallowing and neck pressure symptoms [1][2][3][4]. Patients undergoing thyroidectomy often experience an improvement in quality of life (QoL) three to six months after surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Benign nodular goiter may result in a range of symptoms, including difficulties in swallowing and neck pressure symptoms [1][2][3][4]. Patients undergoing thyroidectomy often experience an improvement in quality of life (QoL) three to six months after surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Reported recurrence rates have not been consistent in the literature, with the average time for recurrence being 10–16 years. Not all patients who have recurrence require reoperation, it was reported that about 10% of patients with unilateral disease might develop recurrence in the long term, but only half will need surgical treatment [ 24 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of retrosternal extension of thyroid goiters may therefore range greatly between 2.6% and 30.4% 4-7 according to the definition used. Causes include various genetic and environmental factors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of retrosternal extension of thyroid goiters may therefore range greatly between 2.6% and 30.4% [4][5][6][7] according to the definition used. Causes include various genetic and environmental factors 8 . Surgery is indicated for retrosternal goiter in the presence of compression symptoms or potential airway compromise and to treat thyroid malignancy.…”
Section: Introductionmentioning
confidence: 99%